Ag-wc-agcu alloy material and method for preparing the same
Patent Information
- Application Number
- CN202611400729.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]针对现有技术存在的不足,本发明的目的在于提供一种Ag-WC-AgCu合金材料及其制备方法,能够克服现有技术中Ag-WC合金组织不均、电阻率波动大、高温抗烧损性能差、成品一致性低的缺陷,通过纳米氧化铜改性配合精准液相还原包覆工艺,实现合金组织结构均匀化,稳定降低材料电阻率,显著提升高温抗烧损与耐电弧性能
[0015]The beneficial effects of this invention are as follows: The invention introduces nano-copper oxide modification, combined with ultrasonic dispersion pretreatment and a peristaltic pump precise drip-feed reduction coating process, resulting in a uniformly dispersed Ag-Cu phase at the interface between the WC matrix and the silver layer. This results in a dense and uniform internal alloy structure with no obvious defects, significantly improving the consistency of the finished product. The nano-Cu element forms an Ag-Cu alloy phase with Ag, which optimizes electron transport channels, reduces interfacial contact resistance, and keeps the alloy resistivity stable at a low level for a long period, effectively preventing problems such as overheating and unstable operation of the equipment. The Ag-Cu composite phase significantly improves the high-temperature stability and interfacial bonding strength of the alloy, effectively suppressing material melting, metal loss, and oxidation burn-off under high-temperature arc erosion, and greatly extending the service life of the material under high-frequency switching, high-current, and high-temperature operating conditions.
Smart Images

Figure CN122913509A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to electrical contact alloy materials, specifically an Ag-WC-AgCu alloy material and its preparation method. Background Technology
[0002] Silver-tungsten carbide (Ag-WC) alloys are widely used electrical contact materials in high and low voltage electrical appliances, switch contacts, relays, and other equipment. They combine the excellent electrical and thermal conductivity of silver with the high hardness, high wear resistance, and high temperature resistance of tungsten carbide, meeting the conductivity and wear resistance requirements under normal electrical contact conditions. However, electrical contact materials are prone to abnormal heating under long-term energized conditions, affecting the operational stability of electrical equipment; secondly, they have weak resistance to high-temperature burn-off and arc erosion. Under high-frequency switching, high-current, and high-temperature conditions, the material surface is prone to arc erosion, metal loss, and local melting defects, shortening the contact life; thirdly, the phase interface bonding is weak, and after repeated thermal cycles, phase separation, cracking, and detachment are prone to occur, reducing the overall mechanical and electrical stability of the material.
[0003] Existing improved processes mostly focus on optimizing powder mixing and sintering parameters, which can only slightly improve material porosity and cannot fundamentally solve the core problems of uneven phase distribution, unstable resistivity, and severe high-temperature burn-off. Furthermore, the modification effect is limited and the process repeatability is poor, making it difficult to meet the stringent requirements of high-precision electrical appliances, high-voltage switches, and high-frequency switching equipment for high uniformity, low stable resistivity, and high burn-off resistance in electrical contact materials. Therefore, developing a process for preparing Ag-WC-based alloys that can precisely control the alloy microstructure, stably reduce resistivity, and significantly improve burn-off resistance has become a key research focus for those skilled in the art. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide an Ag-WC-AgCu alloy material and its preparation method, which can overcome the defects of Ag-WC alloys in the prior art, such as uneven microstructure, large resistivity fluctuations, poor high-temperature burn-off resistance, and low product consistency. By modifying with nano-copper oxide and using a precise liquid-phase reduction coating process, the alloy microstructure is made more uniform, the resistivity of the material is steadily reduced, and the high-temperature burn-off resistance and arc resistance are significantly improved.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing an Ag-WC-AgCu alloy material includes the following steps: S1. Preparation of composite substrate: Tungsten carbide powder and nano copper oxide are dispersed in a liquid medium to obtain a composite substrate in which tungsten carbide powder and nano copper oxide are uniformly dispersed. S2. Preparation of silver ion-containing solution: Dissolve the silver source in a liquid medium to form a solution containing silver ions; S3. Preparation of reducing solution: Prepare a reducing solution containing a reducing agent; S4. Synchronous reduction coating: The silver ion-containing solution and the reducing solution are simultaneously added to the continuously stirred composite bottom liquid to carry out a liquid-phase reduction reaction, so that silver is reduced and deposited on the surface of tungsten carbide particles to form a silver coating layer. At the same time, the nano copper oxide is reduced to copper in situ and forms an Ag-Cu alloy phase with the silver. S5. Post-treatment molding: The product obtained by reduction coating is subjected to solid-liquid separation, drying, reduction and sintering molding in sequence to obtain Ag-WC-AgCu alloy material.
[0006] As a further improvement of the present invention, the particle size of the nano-copper oxide is 50 nm.
[0007] As a further improvement of the present invention, the particle size of the tungsten carbide powder is 1 μm.
[0008] As a further improvement of the present invention, an organic dispersant is also added to the composite base liquid, and the dispersion is carried out by a combination of ultrasonication and stirring.
[0009] As a further improvement of the present invention, the silver source is silver nitrate, and the silver ion-containing solution is a silver ammonium complex ion solution formed by silver nitrate complexing with ammonia.
[0010] As a further improvement of the present invention, the reducing agent is hydrazine hydrate, and the reducing solution is a reducing solution formed by diluting hydrazine hydrate with a liquid medium.
[0011] As a further improvement of the present invention, the synchronous addition is: the silver ion-containing solution and the reducing solution are simultaneously, uniformly, and quantitatively added to the composite base solution by means of a dual peristaltic pump.
[0012] As a further improvement of the present invention, the post-processing molding includes: washing the product obtained by reduction coating until the conductivity of the filtrate is not higher than 100 μS / cm, and then performing vacuum drying, sieving, high-temperature hydrogen reduction, granulation, pressing and sintering under reducing atmosphere protection in sequence.
[0013] As a further improvement of the present invention, the liquid-phase reduction reaction is carried out at room temperature.
[0014] An Ag-WC-AgCu alloy material is also provided, which is prepared by any of the above preparation methods.
[0015] The beneficial effects of this invention are as follows: The invention introduces nano-copper oxide modification, combined with ultrasonic dispersion pretreatment and a peristaltic pump precise drip-feed reduction coating process, resulting in a uniformly dispersed Ag-Cu phase at the interface between the WC matrix and the silver layer. This results in a dense and uniform internal alloy structure with no obvious defects, significantly improving the consistency of the finished product. The nano-Cu element forms an Ag-Cu alloy phase with Ag, which optimizes electron transport channels, reduces interfacial contact resistance, and keeps the alloy resistivity stable at a low level for a long period, effectively preventing problems such as overheating and unstable operation of the equipment. The Ag-Cu composite phase significantly improves the high-temperature stability and interfacial bonding strength of the alloy, effectively suppressing material melting, metal loss, and oxidation burn-off under high-temperature arc erosion, and greatly extending the service life of the material under high-frequency switching, high-current, and high-temperature operating conditions. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the process of the present invention; Figure 2 This is a low-magnification metallographic image of the composite material of the present invention; Figure 3 This is a high-magnification micrograph of the composite material of the present invention. Detailed Implementation
[0017] The present invention will now be described in further detail with reference to the embodiments shown in the accompanying drawings.
[0018] Reference Figure 1-3 As shown, the preparation method of an Ag-WC-AgCu alloy material in this embodiment includes the following steps: S1. Preparation of composite substrate: Tungsten carbide powder and nano copper oxide are dispersed in a liquid medium to obtain a composite substrate in which tungsten carbide powder and nano copper oxide are uniformly dispersed. S2. Preparation of silver ion-containing solution: Dissolve the silver source in a liquid medium to form a solution containing silver ions; S3. Preparation of reducing solution: Prepare a reducing solution containing a reducing agent; S4. Synchronous reduction coating: The silver ion-containing solution and the reducing solution are simultaneously added to the continuously stirred composite bottom liquid to carry out the liquid phase reduction reaction, so that silver is reduced and deposited on the surface of tungsten carbide particles to form a silver coating layer. At the same time, the nano copper oxide is reduced to copper in situ and forms an Ag-Cu alloy phase with silver. S5. Post-treatment molding: The product obtained by reduction coating is subjected to solid-liquid separation, drying, reduction and sintering molding in sequence to obtain Ag-WC-AgCu alloy material.
[0019] In S1, tungsten carbide powder and nano-copper oxide are dispersed in a liquid medium to form a uniform and stable suspension system. The nano-copper oxide particles are uniformly adsorbed and dispersed around the tungsten carbide particles, laying a uniform distribution foundation for the subsequent in-situ introduction of copper elements and avoiding local agglomeration caused by particle size differences when directly mixing in metallic copper powder. In S2, the silver source dissolves in the liquid medium to form a silver ion-containing solution. The silver ions exist in a stable form in the solution and will not precipitate prematurely, ensuring a continuous and uniform supply of silver ions during the subsequent reduction and coating process. In S3, the reducing agent in the reducing solution provides a mild and controllable reduction motive force for the liquid-phase reduction reaction, and the reduction rate is effectively controlled to avoid excessively rapid reaction leading to silver layer agglomeration. In S4, the silver ion-containing solution and the reducing solution are simultaneously added to the continuously stirred composite bottom liquid, where they uniformly contact each other around the tungsten carbide particles and undergo liquid-phase reaction. In the reduction reaction, silver ions are reduced to silver atoms, which then uniformly nucleate and grow on the surface of tungsten carbide particles, forming a dense and continuous silver coating layer. Simultaneously, nano-copper oxide is reduced in situ to active copper atoms in the reduction system. The copper atoms and the synchronously reduced silver atoms nucleate and grow coherently, forming a continuous Ag-Cu alloy coating layer on the surface of tungsten carbide particles. Copper elements are uniformly distributed in the silver coating layer in the form of atomic-level solid solution or nanoscale dispersion, without macroscopic phase separation or copper phase agglomeration. In S5, residual dispersants, complexes, and reducing agent impurities are removed through solid-liquid separation. Drying treatment prevents powder oxidation and agglomeration. Reduction treatment thoroughly removes oxygen impurities inside the powder and improves the interfacial bonding strength. Sintering achieves powder densification, ultimately obtaining an Ag-WC-AgCu alloy material with uniform structure, stable resistivity, and excellent burn-off resistance. Based on the above solution, the technical problems of increased local contact resistance, uneven arc erosion, weak phase interface bonding, and easy burn-off and loss at high temperatures in Ag-WC alloys can be solved.
[0020] To facilitate the uniformity and stability of the composite substrate, in one optional scheme, the nano-copper oxide particles have a diameter of 50 nm. These nanoscale copper oxide particles possess a high specific surface area and high reactivity, allowing them to easily disperse uniformly and remain stably suspended around tungsten carbide particles in the liquid medium. The active copper atoms formed after in-situ reduction can be uniformly distributed within the silver coating layer in a nanoscale dispersed or atomically dissolved manner. This ensures the continuity and uniformity of the Ag-Cu alloy coating layer composition, solving the technical problem of uneven microstructure caused by macroscopic phase separation of copper elements within the alloy.
[0021] Furthermore, the tungsten carbide powder has a particle size of 1 μm. Tungsten carbide particles of this size have good suspension and dispersibility in the liquid medium, and the particle surface area is moderate, which can provide sufficient nucleation sites for the reduction deposition of silver, so that the silver coating layer completely covers the surface of the tungsten carbide particles, avoiding incomplete coating due to excessively coarse particles and agglomeration and sedimentation due to excessively fine particles.
[0022] To further improve the dispersion effect, in one optional approach, an organic dispersant is added to the composite base liquid, and dispersion is achieved through a combination of ultrasonication and stirring. The organic dispersant adsorbs onto the surface of the powder particles, resulting in a stable and uniform composite base liquid, which can solve the technical problems of unstable base liquid and uneven subsequent coating caused by powder agglomeration.
[0023] Further optimization can be achieved by using silver nitrate as the silver source and silver ion-containing solution as a silver ammonium complex ion solution formed by silver nitrate complexing with ammonia.
[0024] To achieve a mild and controllable reduction process, in one specific structure, the reducing agent is hydrazine hydrate, and the reducing solution is a reducing solution formed by diluting hydrazine hydrate in a liquid medium. Hydrazine hydrate has moderate reducing power, and the reduction rate is further reduced after dilution, resulting in a mild and controllable reduction reaction where silver ions are gradually and uniformly reduced to silver atoms.
[0025] To facilitate precise control of synchronous feeding, one optional scheme involves synchronous addition: a silver ion-containing solution and a reducing solution are simultaneously, uniformly, and quantitatively added to the composite substrate using a dual peristaltic pump. The dual peristaltic pump precisely measures the two liquid streams, ensuring that the silver ion-containing solution and the reducing solution always enter the composite substrate synchronously, uniformly, and quantitatively. The two reactants maintain continuous and uniform contact in the substrate at a constant ratio, keeping the silver reduction and deposition rate stable throughout the process. Silver atoms uniformly nucleate and grow on the surface of the tungsten carbide particles, forming a uniform, dense, and continuous silver coating layer.
[0026] To achieve a high-purity and dense molding effect, in one optional scheme, the post-processing molding includes: washing the product obtained from reduction coating until the conductivity of the filtrate is no higher than 100 μS / cm, followed by vacuum drying, sieving, high-temperature hydrogen reduction, granulation, compaction, and sintering under a reducing atmosphere. The washing process removes residual dispersants, complexes, and reducing agent impurities; vacuum drying removes moisture under negative pressure and low temperature to prevent powder oxidation and agglomeration; sieving achieves uniform particle size classification; high-temperature hydrogen reduction removes residual oxygen impurities inside the powder and improves the interfacial bonding strength; granulation, compaction, and sintering under a reducing atmosphere achieve the densification of the powder, resulting in an alloy material with a dense structure and low porosity. This solves the technical problems of weak interfacial bonding, increased resistivity, and accelerated high-temperature burn-off caused by residual impurities and high internal oxygen content.
[0027] Furthermore, the liquid-phase reduction reaction is carried out at room temperature.
[0028] An Ag-WC-AgCu alloy material is also provided, which is prepared by the above-described method. In this alloy material, the surface of the tungsten carbide hard phase particles is coated with a silver coating layer, and the Ag-Cu alloy phase is distributed within the silver coating layer. Copper elements are uniformly distributed within the silver coating layer in the form of atomic-level solid solution or nanoscale dispersion. The alloy material has no obvious agglomeration or porosity. The Ag-Cu alloy phase optimizes the electron transport channel, reduces the phase interface contact resistance, and improves high-temperature stability and interfacial bonding strength. It can directly meet the stringent requirements of high-precision electrical appliances, high-voltage switches, and high-frequency switching equipment for high uniformity, low stable resistivity, and high burn-off resistance in electrical contact materials.
[0029] The specific implementation is as follows: A wet process for preparing a low-resistivity burn-off alloy with a uniform Ag-WC-AgCu microstructure by adding nano-copper oxide includes the following steps: S1. Preparation of composite substrate: Take 682g of tungsten carbide powder with a particle size of 1μm, 5.5g of copper oxide nanoparticles with a particle size of 50nm, add 0.8g of polyvinylpyrrolidone dispersant, add pure water to prepare a solution and bring the volume to 4L. Use 300W ultrasonication and 400 r / min stirring for 30 min to obtain a uniform and stable composite substrate. S2. Preparation of silver ammonium complex ion solution: Dissolve 495 g of silver nitrate solid in 1 L of pure water, stir until completely dissolved, slowly add ammonia water until the solution becomes clear, continue stirring for 20 min to complete the complexation reaction, dilute with water to a silver ion concentration of 1.46 mol / L to obtain a clear silver ammonium complex ion solution.
[0030] S3. Preparation of reducing solution: Take 100 ml of hydrazine hydrate with a concentration of 10-50% and add pure water to prepare 2L of reducing solution. Stir at a rate of 225 r / min.
[0031] S4. Precise reduction coating: Control the stirring speed of the bottom liquid at 500 r / min, and use a dual peristaltic pump to simultaneously add silver ammonium complex ion solution and reducing solution at a rate of 50 mL / min. The reaction temperature is 30℃, and the reaction is continued for 50 min to complete the uniform silver coating on the surface of tungsten carbide particles and generate composite precursor powder. S5. Post-processing and molding: The precursor powder was repeatedly washed with pure water until the conductivity of the filtrate was ≤100μS / cm. It was then placed in a vacuum drying oven and dried at 70℃ and -0.01MPa for 10h. It was then sieved and graded using a 100-mesh sieve. Subsequently, it was reduced at 400℃ and hydrogen flow rate of 100 mL / min for 3h. After reduction, the powder was granulated and pressed into a blank under a pressure of 200MPa for 5 min. Finally, it was sintered at 1000℃ under a reducing protective atmosphere for 2h. After cooling, Ag-WC-AgCu alloy material was obtained.
[0032] Testing revealed that the alloy material prepared in this embodiment has a uniform microstructure without agglomeration or obvious porosity defects, a room temperature resistivity of 2.5 μΩ·cm, and a high-temperature burn-off rate of 1.0% at 1000℃, exhibiting excellent electrical properties and burn-off resistance.
[0033] Example 2
[0034] S1. Preparation of composite substrate: Take 682g of tungsten carbide powder with a particle size of 1μm, 5.5g of submicron copper powder with a particle size of 1μm, add 0.8g of polyvinylpyrrolidone dispersant, add pure water to prepare a solution and bring the volume to 4 L. Use 300W ultrasonication and 400 r / min stirring for 30 min to obtain a uniform and stable composite substrate. S2. Preparation of silver ammonium complex ion solution: Dissolve 495 g of silver nitrate solid in 1 L of pure water, stir until completely dissolved, slowly add ammonia water until the solution becomes clear, continue stirring for 20 min to complete the complexation reaction, dilute with water to a silver ion concentration of 1.46 mol / L to obtain a clear silver ammonium complex ion solution.
[0035] S3. Preparation of reducing solution: Take 100 ml of hydrazine hydrate with a concentration of 10-50% and add pure water to prepare 2L of reducing solution. Stir at a rate of 225 r / min.
[0036] S4. Precise reduction coating: Control the stirring speed of the bottom liquid at 500 r / min, and use a dual peristaltic pump to simultaneously add silver ammonium complex ion solution and reducing solution at a rate of 50 mL / min. The reaction temperature is 30℃, and the reaction is continued for 50 min to complete the uniform silver coating on the surface of tungsten carbide particles and generate composite precursor powder. S5. Post-processing and molding: The precursor powder was repeatedly washed with pure water until the conductivity of the filtrate was ≤100μS / cm. It was then placed in a vacuum drying oven and dried at 70℃ and -0.01MPa for 10h. It was then sieved and graded using a 100-mesh sieve. Subsequently, it was reduced at 400℃ and hydrogen flow rate of 100 mL / min for 3h. After reduction, the powder was granulated and pressed into a blank under a pressure of 200MPa for 5 min. Finally, it was sintered at 1000℃ under a reducing protective atmosphere for 2h. After cooling, Ag-WC-AgCu alloy material was obtained.
[0037] Results Analysis Metallographic microstructure characterization of the Ag-WC-AgCu composite electrical contact material prepared in Example 1 was performed, and the results are shown in Figures 2 and 3, respectively. As can be seen from the low-magnification metallographic structure (Figure 2), the overall structure of the composite material is uniform and dense, with the WC hard phase dispersed uniformly distributed in the silver matrix, without obvious phase segregation, porosity, or macroscopic compositional gradient. Under high-magnification microstructure (Figure 3), no independently existing micron-sized Cu elemental particles were observed, nor were there any locally enriched clusters of copper phase.
[0038] The above-described microstructure indicates that during the liquid-phase chemical coating reaction, the introduced nano-CuO is fully reduced in situ to active Cu atoms in an alkaline hydrazine hydrate reduction system. These Cu atoms then undergo synergistic nucleation and coherent growth with the synchronously reduced Ag atoms, ultimately forming a continuous Ag-Cu alloy coating layer on the WC particle surface. Cu elements are uniformly distributed within the silver coating layer in the form of atomic-level solid solution or nanoscale dispersion, without macroscopic phase separation or copper phase agglomeration. This homogenized microstructure effectively avoids localized increases in contact resistance and uneven arc erosion caused by copper phase segregation, providing a core microstructure basis for achieving low impedance and high ablation resistance in the composite material's service performance.
[0039] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing an Ag-WC-AgCu alloy material, characterized in that, Includes the following steps: S1. Preparation of composite substrate: Tungsten carbide powder and nano copper oxide are dispersed in a liquid medium to obtain a composite substrate in which tungsten carbide powder and nano copper oxide are uniformly dispersed. S2. Preparation of silver ion-containing solution: Dissolve the silver source in a liquid medium to form a solution containing silver ions; S3. Preparation of reducing solution: Prepare a reducing solution containing a reducing agent; S4. Synchronous reduction coating: The silver ion-containing solution and the reducing solution are simultaneously added to the continuously stirred composite bottom liquid to carry out a liquid-phase reduction reaction, so that silver is reduced and deposited on the surface of tungsten carbide particles to form a silver coating layer. At the same time, the nano copper oxide is reduced to copper in situ and forms an Ag-Cu alloy phase with the silver. S5. Post-treatment molding: The product obtained by reduction coating is subjected to solid-liquid separation, drying, reduction and sintering molding in sequence to obtain Ag-WC-AgCu alloy material.
2. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The particle size of the nano-copper oxide is 50 nm.
3. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The particle size of the tungsten carbide powder is 1 μm.
4. The preparation method of the Ag-WC-AgCu alloy material according to claim 1, characterized in that, An organic dispersant is also added to the composite base liquid, and it is dispersed by a combination of ultrasonication and stirring.
5. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The silver source is silver nitrate, and the silver ion-containing solution is a silver ammonium complex ion solution formed by the complexation of silver nitrate with ammonia.
6. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The reducing agent is hydrazine hydrate, and the reducing solution is a reducing solution formed by diluting hydrazine hydrate with a liquid medium.
7. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The synchronous addition refers to the simultaneous, uniform, and quantitative addition of the silver ion-containing solution and the reducing solution to the composite base solution using a dual peristaltic pump.
8. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The post-processing molding includes: washing the product obtained by reduction coating until the conductivity of the filtrate is not higher than 100 μS / cm, and then sequentially performing vacuum drying, sieving, high-temperature hydrogen reduction, granulation, pressing, and sintering under a reducing atmosphere.
9. The method for preparing the Ag-WC-AgCu alloy material according to claim 1, characterized in that, The liquid-phase reduction reaction is carried out at room temperature.
10. An Ag-WC-AgCu alloy material, characterized in that, It is prepared by any one of claims 1 to 9.